Strategies to Improve the Quality for Graduates of State Islamic Higher Education in Aceh - Ulya, Zikriatul; FW Pospos, Ade Fadillah (CV. Rayyan Dwi Bharata, 2024)
This study aims to analyze the impact of strategic planning, the implementation strategy, the evaluation strategy, and to improve the quality for graduates of Islamic State Higher Education in Aceh. The type of data used is the primary data by distributing questionnaires to the Chairperson of the faculty of Economics and Islamic Business of the State Islamic higher education in Aceh, where the analysis tool used was multiple linear regression. The results showed that partially the variety of strategic planning, implementation strategy, and evaluation strategy had a positive impact on improving the quality of graduates. This study concludes that the strategic planning made is still imperfect. The chairperson of the study program must be able to analyze what will be happening in the future, as well as prepare solutions to deal with unwanted situations. Therefore, the planning that has been done will always be able to operate as intended